Quality Characteristics and Shelf Life of Smoked Skipjack Fish (Katsuwonus pelamis L) - Paputungan, Mohammad Reza; Onibala, Hens; Harikedua, Silvana D.; Salindeho, Netty; Mongi, Eunike L.; Mentang, Feny; Tappy, Miranto Stevanus (Sam Ratulangi University, 2023)
One of the typical fishery products of North Sulawesi is whole smoked skipjack which is still traditionally processed. The purpose of this study was to determine the quality of whole smoked skipjack during storage at room temperature in terms of moisture content, total plate count, total mold, and organoleptic value. The results showed that the organoleptic value, moisture content, total bacteria, and total mold only met the Indonesian National Standard on day 0 of storage and exceeded the limit on day 3 of storage. Keywords: Smoked Skipjack tuna; Moisture content; Total Plate Count; Mold Abstrak Salah satu produk perikanan khas Sulawesi Utara adalah ikan cakalang asap utuh yang masih diolah secara tradisional. Tujuan dari penelitian ini untuk mengetahui mutu ikan cakalang asap utuh selama penyimpanan pada suhu ruang dilihat dari kadar air, angka lempeng total, total kapang dan nilai organoleptik. Hasil penelitian menunjukkan bahwa nilai organoleptik, kadar air, total bakteri dan total kapang hanya memenuhi Standar Nasional Indonesia pada penyimpanan 0 hari dan sudah melewati batas pada hari ke-3 penyimpanan. Kata kunci: Cakalang asap; Mutu; Kadar air; Angka Lempeng Total; Kapang